2005
DOI: 10.1016/j.pain.2005.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Activity of masticatory muscles in subjects with different orofacial pain conditions

Abstract: The existence of a pathophysiological link between tonic muscle activity and chronic muscle pain is still being debated. The purpose of this retrospective, controlled study was to evaluate the electromyographic (EMG) activity of masticatory muscles in subjects with different orofacial pain conditions. The temporal and masseter EMG activity at rest and the masseteric reflex were recorded in two groups of patients with either myofascial pain (n=33) or neuropathic pain (n=20), one group of non-pain patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 51 publications
5
44
0
6
Order By: Relevance
“…It has been reported that orofacial pain modulates the activity of the jaw muscles (2) and jaw-stretch reflex (2,30,37,41), suggesting that changes in the functional properties of the jaw muscles mediated by trigeminal nociceptive inputs play an important role in the development of functional disorders of the masticatory system, including temporomandibular disorders. The hemodynamics in skeletal muscles, including jaw muscles, are widely recognized as one of the most important factors for maintaining muscle function (8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that orofacial pain modulates the activity of the jaw muscles (2) and jaw-stretch reflex (2,30,37,41), suggesting that changes in the functional properties of the jaw muscles mediated by trigeminal nociceptive inputs play an important role in the development of functional disorders of the masticatory system, including temporomandibular disorders. The hemodynamics in skeletal muscles, including jaw muscles, are widely recognized as one of the most important factors for maintaining muscle function (8).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies (5,7,9,10) have shown that patients with TMD, compared to asymptomatic patients, showed alterations in the activity of the masticatory muscles during chewing. However, the cited studies are not conclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Since oral contraceptives are being suggested to increase pain and risk of TMD, [11] [12] the present study intended to evaluate the influence of oral contraceptive intake and menstrual cycle on the electrical activity and pressure pain threshold from anterior temporal and masseter mus-cles. A number of studies used rest position to analyses alterations in muscle electrical activity [21]- [23] [25] [26]. As our study was performed with asymptomatic women, we did not find any variation in electrical activity at rest position of oral muscles PPTs during different phases of the menstrual cycle.…”
Section: Discussionmentioning
confidence: 65%